2017
DOI: 10.1016/j.beth.2017.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Trait Affect, Emotion Regulation, and the Generation of Negative and Positive Interpersonal Events

Abstract: Positive and negative trait affect and emotion regulatory strategies have received considerable attention in the literature as predictors of psychopathology. However, it remains unclear whether individuals‟ trait affect is associated with responses to state positive affect (positive rumination and dampening) or negative affect (ruminative brooding), or whether these affective experiences contribute to negative or positive interpersonal event generation. Among 304 late adolescents, path analyses indicated that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 54 publications
(67 reference statements)
4
30
0
Order By: Relevance
“…The findings made in this study reported evidence of transdiagnostic models composed of higher-order factors in terms of externalizing psychopathology [22,23,25,26], negative affectivity as distinctive trait [24,25,27], and impulsivity related to sensation-seeking [21,26,30]. Variables that are constituted as evidence of a transdiagnostic structural model of AD.…”
Section: Qualitative Synthesissupporting
confidence: 52%
See 1 more Smart Citation
“…The findings made in this study reported evidence of transdiagnostic models composed of higher-order factors in terms of externalizing psychopathology [22,23,25,26], negative affectivity as distinctive trait [24,25,27], and impulsivity related to sensation-seeking [21,26,30]. Variables that are constituted as evidence of a transdiagnostic structural model of AD.…”
Section: Qualitative Synthesissupporting
confidence: 52%
“…Another alteration has been a positive and negative affect as a trait since it increases the use of emotional regulation strategies at the interpersonal level in a negative way (externalizing problems). Also, when people have a low positive affect trait are at greater risk of generating interpersonal problems by decreasing functional interaction with others; in addition to the increase in the pattern of avoidance and the deterioration of interpersonal relationships, which leads to opportunities for learning skills that regulate emotional responses in adolescents and youth [24].…”
Section: Emotional Dysregulation Motivation and Cognitionmentioning
confidence: 99%
“…However, the findings for positive affectivity contradicted my prediction. Past research suggests positive affectivity is related to positive rumination (Hamilton et al, 2017), characterized by amplifying one's positive affective experiences. While employees high in positive affect likely still discuss their problems at work, their discussions may focus more strongly on the positive aspects of their issues.…”
Section: Discussionmentioning
confidence: 99%
“…Research suggests that positive rumination is a protective factor against depression (Feldman, Joormann, & Johnson, 2008). In one study, trait positive affect was found to be positively associated with positive rumination (Hamilton et al, 2017). Further, those high in trait positive affect were less likely to engage in dampening, a positive rumination strategy characterized by downgrading one's response to positive affect (Hamilton et al, 2017).…”
Section: Affect and Co-ruminationmentioning
confidence: 99%
See 1 more Smart Citation